2018
DOI: 10.1177/1753193418788935
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of radialization for radial longitudinal deficiency: 20 limbs with minimum 5-year follow-up

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The distal ulna hypertrophied to 97% of the opposite distal radius. 27 The median loss of correction of hand-forearm angle was 9 0 . 27 All hands improved on the assessment scores demonstrating the benefit of radialization.…”
Section: Radializationmentioning
confidence: 94%
See 3 more Smart Citations
“…The distal ulna hypertrophied to 97% of the opposite distal radius. 27 The median loss of correction of hand-forearm angle was 9 0 . 27 All hands improved on the assessment scores demonstrating the benefit of radialization.…”
Section: Radializationmentioning
confidence: 94%
“…27 The median loss of correction of hand-forearm angle was 9 0 . 27 All hands improved on the assessment scores demonstrating the benefit of radialization. However, the authors suggested the need for secondary procedures for long-term maintenance of wrist alignment and hand function.…”
Section: Radializationmentioning
confidence: 94%
See 2 more Smart Citations
“…Radial club hand (RCH) or radial dysplasia is a complex congenital difference occurring in a longitudinal direction resulting in radial deviation of the wrist and shortening of the forearm. In this condition, hand radially deviated at the distal forearm in the shape of a golf club [[1], [2], [3]]. Bone disorders are the most important part of RCH, but abnormalities of muscles, arteries, nerves and joints can greatly affect the function and treatment of upper limb [4].…”
Section: Introductionmentioning
confidence: 99%